A cross-sectional study to determine sex-wise prevalence of obesity in adults of Kashmiri population - Shirazi, Ibrar Bashir; Hamid, Sajad; Rafiq, M.; Hamid, Shahnawaz (International Journal of Research in Medical Sciences, 2017)
Background: Aim of current study was to determine the prevalence of obesity in both sexes in persons aged 18-45 years. Methods: Multistage and multiphasic sampling technique was utilized in this study to screen the obese subjects of both males and females based on WHO classification of obesity according to BMI of 18-45 years of age. Each household was visited and only the subjects having age of 18-45 years were included in this study and this comprised of 5107 subjects, then identified obese cases with the help of height and weight techniques. Only those people who had simple obesity were included in the study. People having secondary obesity, drug induced obesity and pregnant ladies were excluded from this study. The data was collected and analysed using statistical software and chi square and proportional statistical test were applied. Results: Out of 5107 screened population, 2652 were males and 2455 were females and the prevalence of male obesity in study population is 6.41% and that of females is 7.74%. Conclusion: The sex has a significant impact on obesity. We reported in our study a prevalence of obesity is more in females as compared to males. A lack of physical activity as well as low frequency of employment makes females more susceptible to obesity.